Developing Students’ Digital Skills: A Case Study at Hanoi University of Science and Technology - Bui Thanh Thuy; Dinh Dieu Ly; Do Hong Son (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
The research was undertaken to evaluate the level of digital skills of 196 students from Hanoi University of Science and Technology. Findings show that students demonstrate a good understanding and grasp of necessary digital skills, especially locating information and communication skills. However, digital content creation skills and digital empathy skills need improvement. Results indicate no significant difference in digital skills between genders, fields of study, and internet usage per day. However, the level of digital skills tends to decrease slightly from the first to the fourth year, indicating that students are becoming more aware of the need to continuously learn and develop digital skills. Some solutions proposed to enhance students’ digital skills over the course of their degree include: integrating specialized courses and workshops into the already existing training program; continuously offering courses on new technologies; enhancing university facilities and technology; integrating real-world projects and internship opportunities to boost digital skills; and developing tools and courses that allow students to self-assess their digital skills and receive feedback from teachers who can support them in improving their capabilities. Received 11th February 2024; Revised 4th March 2024; Accepted 7th April 2024